2020
DOI: 10.1016/j.lfs.2020.117361
|View full text |Cite
|
Sign up to set email alerts
|

Effect of superparamagnetic iron oxide nanoparticles on glucose homeostasis on type 2 diabetes experimental model

Abstract: Evaluation of the anti-diabetic effect of superparamagnetic iron oxide nanoparticles (SPIONs) on Type 2 diabetic rats and compared their effect to metformin treatment. Main methods: Diabetic rats were treated with different doses of nanoparticles one time per week for 4 weeks. Fasting blood glucose level was determined for studied groups during the experimental period (30 days). At the end of the experiment, oral glucose tolerance test was carried out, serum samples were collected for biochemical assays. Then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…The positive control metformin-treated cells showed a cellular glucose uptake of 72.46 ± 2.4%, which is lesser than CS/PVA-PD-FeO NPs. Similarly, earlier work has reported that superparamagnetic iron oxide nanoparticles (SPION) significantly reduce the blood glucose level in diabetic rats more so than metformin [ 73 ]. In addition, SPION was found to regulate the expression of obesity and type-2 diabetic-related genes in human preadipocyte cells [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…The positive control metformin-treated cells showed a cellular glucose uptake of 72.46 ± 2.4%, which is lesser than CS/PVA-PD-FeO NPs. Similarly, earlier work has reported that superparamagnetic iron oxide nanoparticles (SPION) significantly reduce the blood glucose level in diabetic rats more so than metformin [ 73 ]. In addition, SPION was found to regulate the expression of obesity and type-2 diabetic-related genes in human preadipocyte cells [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Also, Deng et al (2021) [15] tested their biocompatible 4 nm SPIONs, observed no damages in the hepatic tissues, and showed the safe applicability of those NPs as contrast agents. The use of SPIONs-PEG in vivo was reported before [68,69]; however, no other studies are investigating the distribution and histopathological effects of 50 nm SPION-PEG clusters on filtering organs (liver, spleen, kidney) as far as we are aware.…”
Section: Discussionmentioning
confidence: 99%
“…Superparamagnetic iron oxide nanoparticle-based nanowarming has demonstrated the potential to be a revolutionary technology for the field of cryopreservation, which is invaluable for cell, tissue, and organ banking. The SPIONs-based magnetothermal effect has also been utilized in other biomedical areas such as glucose regulation [143,144]. For instance, Stanley et al decorated a modified temperature-sensitive channel, TRPV1, with antibodycoated SPIONs which were heated with a low-frequency magnetic field to regulate the protein production [145].…”
Section: Nanowarmingmentioning
confidence: 99%